Assessing stability and performance of fluorine-doped tin oxide electrodes for peroxide formation in carbonate-based electrolytes - Romeiro, Fernanda da Costa [UNESP]; Orlandi, Marcelo Ornaghi [UNESP]; Mul, Guido; Wenderich, Kasper; Mei, Bastian (Elsevier, 2023)
Hydrogen peroxide (H2O2) is a valuable chemical currently produced industrially on a large scale by the anthraquinone process. Recently, carbonate and/or bicarbonate-induced selective water oxidation to hydrogen peroxide has been suggested as an environmentally friendly alternative. In this manuscript, we discuss the effect of electrolyte concentration and type of cation in selective water oxidation using carbonate-based electrolytes (i.e., Na2CO3, K2CO3 and Cs2CO3) on fluorine-doped tin oxide (FTO) electrodes. Based on the experimental observations and a techno-economic evaluation we reveal that K2CO3 is preferred over Na2CO3 and Cs2CO3 electrolytes. Using 5 M K2CO3 a Faradaic efficiency of > 60 % was achieved at industrially relevant current densities of 100 mA cm−2. Although for 5 M Cs2CO3 electrolytes lower potentials are required at otherwise similar process conditions, a lower efficiency for hydrogen peroxide formation has been observed which is assigned to higher degradation in Cs-containing electrolyte, rendering the use of potassium-based electrolytes more efficient. Independent of the electrolyte used, the electrodes suffered from stability issues as revealed by increasing concentrations of tin in the electrolyte and electrode failure after polarization for several hours. Overall, this work provides detailed knowledge about the impact of electrolyte concentration and type of cation and reveals the importance of appropriate cell design and process operation for meaningful hydrogen peroxide synthesis by mediated-anodic water oxidation.
Keywords: Carbonate; Cations effect; Electrode stability; Fluorine doped-tin oxide; Peroxide